Contestation of the Young Group of Indigenous Forest Guardians in Manurung Village, East Luwu, South Sulawesi (A Political Ecology Review) (Equilibrium: Jurnal Pendidikan, 2026)
This article reviews the role of political ecology of young people in Cerekang Village who are part of the Cerekang Indigenous people. The Cerekang Indigenous People are an area that lives around the Cerekang river and Pismiaoni Hill, Manurung Luwu Village, East South Sulawesi. The Cerekang youth group that joined the Pejuang Muda Wija To Cerekang (PMWTC) has been contesting in its role in protecting the environment and customary territories from the destruction of the mining industry and the conversion of land into ponds within the framework of political ecology. This study uses a qualitative descriptive approach with PMWTC youth informants, heads of customary institutions, and local communities selected through purposive sampling. Data analysis is carried out in three stages, namely data reduction, data presentation, and conclusion drawn. This article finds that the contestation of the Cerekang youth group is classified as a political ecological role that is consciously actively involved in organizing and maintaining customary forest areas in the form of spatial emancipation, transformative participation, and ecological schools. In terms of novelty, this research provides a framework for understanding the political role of indigenous youth based on environmental awareness. Thus, political ecology with a direct demonstration of traditional values that position themselves as the vanguard of the guardian of customary forest areas from the threat of massive and extractive environmental damage.